Menelusuri Keterkaitan Antara Ajaran Katolik dan Kehidupan Modern di Era Digital - Markus Kandu; Aventus Bito (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The digital era is an era in life where progress is quite rapid and is leading to digital forms. The development of the digital era will continue to run so fast and cannot be stopped by humans. The development of communication in the digital era has also had an impact on the Catholic Church. As a fellowship of God's people who have a divine-human dimension and are on a pilgrimage on earth towards heavenly fullness, the Church's presence in the world aims to be a sacrament of God's salvation so that everyone experiences divine grace that gives them life in abundance. The development of digital technology in this century has of course had an impact on the Catholic Church. Believers need to form digital communities that have special facilities that make them different from other communities, on the other hand stating that in the field of religious expression and praxis, the virtual world has offered a medium for people to gather in the name of faith and spirituality, so that existence Today's digital technology is not seen as a problem. Believers must understand well the positive side of changing times and must have technological competence to be able to create good quality. In this digital era, technology is like a double-edged sword. On the one hand, technology helps connect people and facilitate various aspects of life. But on the other hand, excessive dependence on technology can have an impact on individuals, one of which is alienation from the people around them. In the turbulent modern era, building a strong Catholic faith is like erecting a strong fortress to protect and grow the faith of the people. This faith becomes a forum for strengthening each other, spreading the love of Christ, and facing various challenges of the times. Facing the challenges of the times, namely social and cultural changes, where strong Catholic faith and teachings can help Catholics to face various social and cultural changes that occur in the modern era. Catholic teachings provide a strong moral and spiritual foundation for Catholics to remain firm in their faith and Christian values.